The correlation between the severity of anterior crossbite and skeletal deformities in post-surgery cleft lip and palate among children - Setianingtyas, Prastiwi; Primarti, Risti Saptarini; Riawan, Lucky; Oscandar, Fahmi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Cleft lip and palate is the most common craniofacial malformations, which is a congenital deformity of lip and palate or both. Anterior crossbite is occlusal characteristics that are often found in patients with cleft lip and palate who had surgery, caused by dentoalveolar or skeletal abnormalities, can be distinguished based on the cephalometric analysis. This research was aimed to analyse the correlation between the severity of anterior crossbite and skeletal deformities in post-surgery cleft lip and palate among children. Methods: The research design was an analytic correlation with the sample selection based on purposive sampling. The research was conducted from 14 cleft lip and palate patients in the primary dentition (aged 4-6 years old) who had surgery (for 2-3 years) using analysis of study models and cephalometric digital. Statistical analysis was conducted by Spearman Rank Correlation Coefficient test to analyse the relationship between the severity of anterior crossbite with skeletal deformities. Results: Statistic test showed that 42.86% of the anterior crossbite in the cleft lip and palate post-surgery in primary dentition had a very high level of severity, thus leading to very poor occlusion. As many as 21.43% had a high level of severity, which leads to poor occlusion, and 35.71% had a moderate level of severity, which leads to fair occlusion. The Spearman Coefficient of Rank Correlation test results showed a weak correlation between the severity of anterior crossbite with skeletal deformities with coefficient relation of 0.13 and p-value of 0.48 (p<0.05). Conclusion: There is a weak correlation between the severity of anterior crossbite with skeletal deformities in post-surgery cleft lip and palate among children.